THE DEVELOPMENT OF STRATEGIES TO STRENGTHEN TOOTH ENAMEL AND DENTIN FROM PAST TO PRESENT (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
The integrity and resilience of tooth hard tissues, including enamel and dentin, are critical determinants of oral health and longevity. Throughout history, diverse strategies have been employed to enhance tooth resistance, ranging from ancient dietary and herbal practices to contemporary biomineralization and remineralization therapies.